Promoting Pancasila values through local culture: a case study of the Tengger festival of the karo ethnic group for ecotourism development - Rawanoko, Endrise Septina; Sungkawati, Endang; Ario, Muhammad Fanif (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
Currently, the role of tourism significantly influences the economy of Indonesia. Ecotourism is an environmentally conscious tourism activity that prioritizes the preservation of nature, and empowerment of the local community in terms of social, cultural, and economic aspects, as well as learning and education. In the village of Poncokusumo, the local cultural tradition known as Hari Raya Karo is still preserved to this day. Hari Raya Karo, or Yadnya Karo, is the second major festival after Kasada. This research adopts a qualitative descriptive methodology. The findings from field research encompass the entire series of Hari Raya Karo ceremonies, which can be sequentially described as follows: (1) opening ceremony, (2) sodoran, (3) puja sesanti, (4) andon mangan, and (5) sadranan and tari ojung. On the other hand, the Selamatan Desa ceremony follows the following order: (1) visiting graves, (2) ater tumpeng, (3) tandakan, (4) entertainment, and (5) sadranan. Observing the transition from Hari Raya Karo to Selamatan Desa, ritual changes have occurred. Hari Raya Karo is conducted by the entire Tengger community in the Bromo Mountain region, including those practicing Islam, Hinduism, Buddhism, and Christianity, both in Brang Wetan (Probolinggo and Lumajang Regencies) and Brang Kulon (Malang and Pasuruan Regencies). Conversely, the Selamatan Desa ceremony is explicitly carried out by the residents of Poncokusumo village.